Institutional Culture and Differential Treatment: Faculty Professionalism and Power Dynamics in Higher Education - Nomaan, Saima (Journal of Cultural Analysis and Social Change, 2025)
Equality, fairness, and non-discrimination are widely promoted as core values of professional conduct in contemporary institutions. Yet beneath policy rhetoric, patterns of unequal and differential treatment continue to shape everyday academic life. This longitudinal qualitative study examines how institutional culture, managerial practices, and power dynamics shape faculty experiences of professionalism and fairness in eight higher education institutions. Grounded in an interpretivist-qualitative design, the research draws on twenty-four semi-structured faculty interviews and institutional policy analysis conducted over nine years. It explores how organisational structures, cultural hierarchies, and interpersonal networks mediate perceptions of recognition, belonging, and professional identity. Findings reveal that differential treatment is both a managerial and cultural phenomenon, sustained through implicit hierarchies of nationality, social proximity, and organisational alignment. While institutional policies promote merit and equality, informal practices reproduce symbolic power and selective privilege. Acts of moral resistance and emotional resilience emerge as strategies through which faculty preserve dignity and integrity within hierarchical academic cultures. The study extends organisational-justice theory by situating it within an interpretivist cultural framework, demonstrating how fairness and professionalism are contextually enacted and mediated by institutional culture and power dynamics. It contributes to debates on institutional culture and equity by revealing how differential treatment both reflects and reinforces broader cultural hierarchies in transnational higher education.